The effect of communication media on the uptake of agricultural innovations in selected states of Nigeria - Atser, G.; Dixon, A.; Ekeleme, F.; Hauser, S.; Fadairo, O.; Adekoya, A.; Ayanwale, A.B.; Agada, M.; Oladokun, I.; Akpu, P.; Sanni, L.; Pypers, P.; et al. (Informa UK Limited, 2023)
Purpose Poor uptake of agricultural innovations on weed management practices is a major factor responsible for low productivity. This paper examines how communication media can help improve farmers’ adoption behaviour.